DOES THE RECENTLY IMPLEMENTED REGULATION ON COUNTRY-BY-COUNTRY REPORTING DETER TAX AVOIDANCE? - Kurniawan, Nala; Saputra, Anggari Dwi (UI Scholars Hub, 2020)
To adhere with Base Erosion and Profit Shifting (BEPS) Action 13, Indonesia enacted regulations concerning Transfer Pricing Documentation and Country-by-Country Reporting (CbCR) to address the issue of tax avoidance. Those regulations introduced the requirement of CbCR in Indonesia, where Multinational Enterprises (MNEs) operating in Indonesia are required to provide tax authorities with geographic breakdown of their profitability, tax payments, and activities wherever they operate. Using the newly implemented CbCR in Indonesia as a treatment for private disclosure requirement, this study examines the effect of CbCR on MNEs tax avoidance. Employing EUR 750 million consolidated revenue threshold for disclosure and utilizing regression discontinuity design as well as difference-in-differences analysis, we document a 4-8 percentage point increase in effective tax rates among affected MNEs, thus reflecting a decrease in tax avoidance in treatment firms. Our findings contribute (i) to the recent empirical literature on how CbCR as a private disclosure affects corporate tax avoidance behavior and (ii) to the policy evaluation whether CbCR regulation has achieved its objective.